INVESTIGATION OF ABRASION DISASTERS IN VARIOUS COASTAL COMMUNITIES IN INDONESIA - Palisu, Brian Jaya; Fiqri, Muh Rizal; Assidiq, Fuad Mahfud (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2022)
Indonesia's population is the fourth largest in the world, around 273 million in 2020. And about 60% of them live in coastal areas. Most of them rely on the existence of coastal and marine natural resources. So it is not surprising that most of the daily activities and activities are always related to the existence of resources around the coast. One of the many threats to people living in coastal environments is coastal abrasion. Coastal abrasion is the process of coastal erosion caused by the destructive power of ocean waves and currents. The damage to the coastline is due to the disruption of the natural balance in the coastal area. Abrasion can be caused by nature but also human activities can be the main cause of abrasion. Coasts in various parts of Indonesia are known to have narrowed due to abrasion in recent years. At least 400 kilometers of Indonesia's coastline has been eroded by the disaster, according to data from the Ministry of Fisheries and Maritime Affairs. Without immediate action, much of Indonesia's land is threatened with extinction in the coming years (Kompas, 2019). This disaster can have negative impacts such as damage to community settlements, pond land, and beach tourism, as well as damage to infrastructure or other facilities such as roads, houses, docks, trees, and electricity poles, socio-economic impacts, especially specifically to communities in coastal areas.